Correlation between Interdialytic Weight Gain and Intradialytic Hypotension in Patients with Chronic Kidney Disease Undergoing Hemodialysis in Tertiary Referral Hospital - Artaria Tjempakasari; Nitya Prasanta; Aditiawardana; Magdeline Elizabeth Carrasco (Biomolecular and Health Science Journal)
Introduction: Chronic kidney disease (CKD) is a condition characterized by kidney damage or reduced function lasting at least 3 months. Hemodialysis (HD) is a key treatment for CKD, replacing kidney function in fluid and acid–base electrolyte balance, metabolic waste removal, and blood pressure management. Intradialytic weight gain (IDWG) is a common HD complication, with patients with limited systolic blood pressure having the highest risk of intradialytic hypotension (IDH)-related death. This research examined IDWG patterns in patients on regular HD. Methods: A prospective, observational study of 40 end-stage renal disease patients on regular HD twice a week at Dr. Soetomo Hospital was conducted for 3 months. Every patient received HD for at least 3 months. Data from purposive sampling. Statisticians used IBM SPSS® Statistics 25. Results: A total of 20 out of 40 IDWG subjects experienced IDH. In the IDH group, the percentage of women was 11 (55%) people, the mean age of the research subjects was 49.9 ± 9.70 years, the mean duration on HD of the research subjects was 70.5 ± 43.78 months, and the mean IDWG percentage (IDWG%) of the research subjects was 5.36 ± 1.1. By statistical analysis, a correlation value of P = 0.008 was obtained. Conclusion: There was a correlation between IDWG% and the incidence of IDH, with or without confounding factors such as gender, age, and duration of HD. The higher the percentage value of IDWG, the higher the IDH incidence rate.